2008
DOI: 10.1016/j.ydbio.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Development and tissue origins of the mammalian cranial base

Abstract: The vertebrate cranial base is a complex structure composed of bone, cartilage and other connective tissues underlying the brain; it is intimately connected with development of the face and cranial vault. Despite its central importance in craniofacial development, morphogenesis and tissue origins of the cranial base have not been studied in detail in the mouse, an important model organism. We describe here the location and time of appearance of the cartilages of the chondrocranium. We also examine the tissue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
297
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(314 citation statements)
references
References 63 publications
15
297
1
1
Order By: Relevance
“…In addition to differentiating into cardio vascular cells, Mesp1 GFP cells could also differentiate into skeletal muscle and bone cells (Myogenin, Runx2, and Col1a1; Fig. S1 B), which is consistent with the in vivo Mesp1 lineage tracing experiments that showed that Mesp1 expressing cells give rise to some muscles and bones of the face (McBratney Owen et al, 2008;Yoshida et al, 2008;Harel et al, 2009). However, not all mesoderm derivatives were increased in Mesp1 GFP cells; e.g., no increase in hematopoietic markers, such as Gata1 and HoxB1, was observed.…”
Section: Mesp1-gfp-expressing Cells Represent the Earliest Source Of supporting
confidence: 85%
“…In addition to differentiating into cardio vascular cells, Mesp1 GFP cells could also differentiate into skeletal muscle and bone cells (Myogenin, Runx2, and Col1a1; Fig. S1 B), which is consistent with the in vivo Mesp1 lineage tracing experiments that showed that Mesp1 expressing cells give rise to some muscles and bones of the face (McBratney Owen et al, 2008;Yoshida et al, 2008;Harel et al, 2009). However, not all mesoderm derivatives were increased in Mesp1 GFP cells; e.g., no increase in hematopoietic markers, such as Gata1 and HoxB1, was observed.…”
Section: Mesp1-gfp-expressing Cells Represent the Earliest Source Of supporting
confidence: 85%
“…Using quail-chick chimeras, all layers of the forebrain meninges as well as bone and overlying dermis originate from the cephalic neural crest (Le Lievre and Le Douarin, 1975;Couly and Le Douarin, 1987), whereas the meninges covering the brainstem and spinal cord arise from a different embryological lineage, likely the mesoderm (Catala, 1998). Recent studies using transgenic mice with neural crest (Wnt1Cre)-and mesoderm (Mesp1Cre)-specific promoters have shown that the meninges covering the telencephalon are of neural crest origin, whereas the midbrain meninges derive from the cephalic mesoderm (McBratney-Owen et al, 2008;Yoshida et al, 2008). In this report, we conclusively establish that the inner part of the dura mater (DBC) and the outer part of the arachnoid (ABC) derive from a common PGDS ( þ ) precursor cell.…”
Section: Discussionmentioning
confidence: 53%
“…It should be noted, however, that the endothelial cells of the stromal vessels from the forebrain choroid plexuses originate from the cephalic mesoderm and not from the neural crest as the rest of the connective tissue of the stroma [27]. In mice, such a dichotomy in the origin of the sus-and sub-tentorial meninges (and choroidal stroma) was also demonstrated [92].…”
Section: Understanding Choroid Plexus Developmentmentioning
confidence: 99%